Caricom : regional programming paper (IDB [New York]us, 1998)
Reviews the current status of the integration process in CARICOM. Proposes a Bank regional strategy for CARICOM and presents a plan of action based on the strategy. Summarizes current international donor activities in CARICOM. Provides a comprehensive background analysis of Caribbean regional integration and development, and a statistical overview that includes general economic and trade data for the subregion as a whole and for individual Caribbean countries.
Contents : v.1. Main report. - v.2. Background analysis and annexes